2020
DOI: 10.1016/j.devcel.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs and Neural Alternative Polyadenylation Specify the Virgin Behavioral State

Abstract: How are diverse regulatory strategies integrated to impose appropriately patterned gene expression that underlie in vivo phenotypes? Here, we reveal how coordinated miRNA regulation and neural-specific alternative polyadenylation (APA) of a single locus controls complex behaviors. Our entry was the unexpected observation that deletion of Bithorax-Complex (BX-C) miRNAs converts virgin female flies into a subjective post-mated behavioral state, normally induced by seminal proteins following copulation. Strikingl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 65 publications
1
38
0
Order By: Relevance
“…We employed SAG-1 neurons for quantitative analysis of Hth and Dsx within identified VNC nuclei, taking great care to stain wild-type and mutant VNC in the same wells and to image them in parallel using identical settings (see Methods). Although SAG-1 neurons did not necessarily accumulate the highest levels of Hth seen amongst total VT-7068 or VT-50405 neurons (Garaulet et al, 2020), we could reliably observe elevated Hth in identified SAG-1 neurons, in both miRNA deletion and hth [BSmut] mutants, concomitant with downregulation of Dsx ( Figure 2G). In these same SAG-1 neurons, wildtype Dsx exhibits a somewhat bimodal distribution ( Figure 2G).…”
Section: Mutually Exclusive Expression Of Hth and Dsx Is Disrupted Bymentioning
confidence: 78%
See 4 more Smart Citations
“…We employed SAG-1 neurons for quantitative analysis of Hth and Dsx within identified VNC nuclei, taking great care to stain wild-type and mutant VNC in the same wells and to image them in parallel using identical settings (see Methods). Although SAG-1 neurons did not necessarily accumulate the highest levels of Hth seen amongst total VT-7068 or VT-50405 neurons (Garaulet et al, 2020), we could reliably observe elevated Hth in identified SAG-1 neurons, in both miRNA deletion and hth [BSmut] mutants, concomitant with downregulation of Dsx ( Figure 2G). In these same SAG-1 neurons, wildtype Dsx exhibits a somewhat bimodal distribution ( Figure 2G).…”
Section: Mutually Exclusive Expression Of Hth and Dsx Is Disrupted Bymentioning
confidence: 78%
“…To be certain of this effect, we quantified all Dsx+ neurons throughout the volume of the VNC, and observed ~150 fewer Dsx+ neurons in both mutant conditions (Figure 2E), but found that the difference was larger when restricting the analysis to the dorsal half of the VNC (Figure 2E). We recently showed that repression of hth by BX-C miRNAs that is relevant for female PMRs occurs in several populations of abdominal VNC neurons, marked by the VT-7068, VT-454 and VT-50405 Gal4 drivers (i.e., VT-switch lines) (Feng et al, 2014;Garaulet et al, 2020). However, the numbers of neurons labeled by these drivers (~80-300) were not substantially affected in miRNA mutants ( Figure 2F).…”
Section: Mutually Exclusive Expression Of Hth and Dsx Is Disrupted Bymentioning
confidence: 91%
See 3 more Smart Citations